Forest genetic resources conservation and management: National consultative workshops of seven South and Southeast Asian countries - Choo, K.Y.; Jalonen, R.; Hong, L.T.; Sim, H.C. (2009)
The reports included in this volume come from seven national consultative workshops within the ITTO funded project on forest genetic resources, ”Strengthening National Capacity and Regional Collaboration for Sustainable Use of Forest Genetic Resources in Tropical Asia”. The project started in February 2006 and ended in 2009, and was carried out by seven participating countries: Cambodia, India, Indonesia, Malaysia, Myanmar, the Philippines and Thailand. This volume results from a collaboration amongst FRIM, Bioversity International and APAFRI.